Ativos intangíveis e riscos de mercado e idiossincrático nas empresas de capital aberto brasileiras - Silva, Pedro Jorge Pinheiro da (2025)
This study examined the relationship between recognized intangible assets and the market and idiosyncratic risks of non-financial Brazilian publicly traded companies with shares listed on Brazil Bolsa Balcão (B3). The research sample covers Brazilian companies listed on B3 between 2010 and 2023, excluding financial companies and those with missing data and outliers, resulting in two samples: 243 companies and 1,721 observations for representativeness analysis, and 217 companies and 1,533 observations for the composition of intangible assets analysis. Market risk () and idiosyncratic risk (), measured using the Capital Asset Pricing Model (CAPM), were obtained using the R software, while data on intangible assets were collected from the Balance Sheet, Notes to the Financial Statements, and Economática®. Intangible assets were evaluated based on their representativeness by total assets () and non-current assets () and by their composition of human assets (), innovation (), structural (), relationship (), goodwill (), and others (), given that part of this classification was proposed by Kayo and Famá (2004). For analysis, descriptive statistics, trend tests (Jonckheere–Terpstra), median difference tests (Kruskal–Wallis and Mann–Whitney), and multiple linear regression with panel data were employed. The results show that intangible assets vary across sectors and by degree of intangibility and exhibit a growth trend between 2010 and 2023. The representativeness and composition of intangible assets were distinct across sectors, but only the composition of human assets, relationship assets, and other assets increased during the analyzed period. The research findings also suggest that, in addition to growing during the analyzed period, market and idiosyncratic risks are distinct across sectors. Furthermore, the evidence indicates that market risks are higher when companies have a greater amount of intangible assets. Regression analyses revealed that the representativeness of intangible assets relative to non-current assets increases the market risk of companies, while the composition of relationship assets decreases it. No evidence was found to suggest that intangible assets influence idiosyncratic risk. It is concluded that, according to the theoretical assumptions of the Resource-Based View and the Efficient Market Hypothesis, intangible assets increase the market risk of companies, with sectoral and temporal variations, but do not affect idiosyncratic risk. This study provides practical contributions by offering insights for investors and managers on how the management of intangible assets can affect a company's market risk, aiding in informed decision-making within different sectors.